Development of a tool to evaluate the impact of modications within subsystems for an FSAE electric virtual prototype using Adams suite (2017)
"This graduation project is a tool that allows identifying the effect that modifications over some vehicle parameters have in the overall performance of the vehicle in the cornering and straight line maneuvers. The assessment of these effects was made using the ADAMS package of MSC software. The project contains the following as part of the tool: A diagram of concepts and vehicle dynamics relations and an annex document that details every concept on the diagram. An enlarged database of the virtual prototype of the Formula SAE in Adams Car. An user guide of Adams Car and Adams Insight as an annex document. A methodology that allows identifying and quantifying the effects that modifications of different parameters have on the vehicles overall performance." -- Tomado del Formato de Documento de Grado.